The representation of a legal entity by its head in criminal proceedings in the aspect of the introduction of advocacy monopoly - Yakymchuk, Olha (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article analyzes the theoretical and practical aspects of the representation of a legal entity by its head and other person authorized by the founding documents or by law in criminal proceedings in the context of amending the Constitution of Ukraine regarding the representation of another person in court exclusively by advocate